Risk Assessment of Malaysia’s Maritime Supply Chain Security in Seaports and Waterways - Roh, Saeyeon; Tam, Jason; Lee, Sung-Woo; Seo, Young-Joon (International Journal of Supply Chain Management, 2018)
With the increase in terrorism and piracy threats around the world, the issue is not if an attack will occur, but where and when it will come. Ports and waterways are crucial for international trade, and damage to them may cost millions to the global economy. In the past, Malaysia has been threatened and attacked by terrorists, and pirates have hijacked ships near the coasts of the Strait of Malacca and the South China Sea. Such acts can negatively affect the country’s maritime supply chain. This research analyses the risk to Malaysia’s maritime supply chain security in ports and waterways by applying a risk assessment matrix. The findings show that Malaysian ports are vulnerable to attacks and crime due to various factors. Also, Malaysia’s waterways may always be at risk given the country’s geographical location and status as one of the most important trade routes in the world. Mitigating the risk to ports and waterways can be accomplished by investing in more advanced security equipment, eliminating corruption, and increasing the military presence in the Strait of Malacca. This research may be able to help increase ports’ policy-makers’ preparation and decision-making, helping them to address risks to ports and waterways in Southeast Asia.